Redesigning Innovation and Entrepreneurship Education in Chinese Tier-2 Universities: A 6E Model for Global-Local Integration - Zeng Lin; Astri Yulia; Xie Linjian (Research Synergy Foundation, 2025)
This study uses a mixed-method approach to examine the alignment of innovation and entrepreneurship (I&E) education in Chengdu's tier-2 universities with global frameworks and local industry needs. Textual analysis of 9 curricula is benchmarked against Disciplined Entrepreneurship, HEInnovate, and EntreComp, revealing gaps in customer validation (22% include MVP design), practical application (33% have prototypes), digital literacy, and cross-cultural competence. Focus group discussions with eight industry and faculty stakeholders, as well as surveys of 303 students, 40 teachers, and 41 HR professionals, triangulate these findings, showing that 82% of enterprises rate graduates' digital skills as below average. The proposed 6E model (Engage-Extend) redesigns curricula to integrate global competencies with local demands (e.g., Chengdu's digital economy), emphasising experiential learning via industry projects and micro-credentialing. The framework addresses transferable skill gaps (stress resilience, creativity) and boosts employability, with mediational analysis showing an R² of 0.365 in explanatory power. The study concludes by outlining the curriculum and advocating longitudinal research on its impact and technological integration under China's